Towards the enhancement of nuclear reactor safety: Physical phenomena involved in the measurement accuracy of boron concentration online monitoring systems - Tabti Nouhaila; Sari Adrien; Tromson Dominique (EPJ Web of Conferences, 2023)
In Pressurized Water Reactors (PWRs), boron10 (10B) is added to the primary fluid as boric acid to regulate criticality and power distribution within the core. Indeed, 10B possesses a significant neutron absorption cross-section of approximately 3845 barns for thermal neutron energy (around 25.3 meV). Thus, under certain circumstances, even a slight variation in boron concentration could lead to criticality issues. This paper addresses the problems regarding the accuracy and real-time measurement of Boron Concentration Online Monitoring Systems (BCOMS) in PWRs. First, the paper focuses on presenting BCOMS’s key performance and qualification criteria to ensure a real-time, accurate response during normal operation, operational transients, and accidental events. Then, we evaluate the influence of different dimensioning parameters on the overall measuring performance through Monte Carlo simulations using the MCNP6.2 code. Finally, we investigate, combining theoretical knowledge and simulation results, the physical phenomena involved in the measurement accuracy of BCOMS. This analytical approach not only fosters a deeper comprehension of the underlying phenomena but also facilitates the identification of potential areas for improving measurement accuracy, thereby enhancing the safety of nuclear reactors.